(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study evaluated the effectiveness of counseling on recommended water supplementation for adults, conducted at the School of Preventive Medicine and Public Health from April to December 2024. Methods: Results: The results showed that the percentage of individuals consuming less than 75% of the recommended daily water intake was 42.9% before the intervention, which decreased to 22.9% after three months. The average daily water consumption increased from 1200 (1100 – 1500) mL before the intervention to 1563 (1316 – 1708)mL after the intervention, a statistically significant difference (p < 0.05). Symptoms and frequency of upper respiratory tract diseases improved, with the proportion of individuals without respiratory symptoms in the last three months increasing from 2.9% to 20% (p = 0.014). Regarding subclinical indicators, serum IgA concentration significantly increased from 236 (188-274) mg/dL to 241,1 (190-293) mg/dL (p = 0.0005). No statistically significant difference was found in gastrointestinal symptoms. Conclusion: Counseling on recommended water supplementation effectively improved daily water consumption., The increased blood IgA levels and reduced frequency and symptoms of respiratory in the study subjects suggest a direction for further in-depth research into the role of hydration and immunosuppressive water in the future